Disentangling the relationship between cholesterol, aggression, and impulsivity in severe mental disorders. Issue 9 (17th July 2020) - Hjell, Gabriela; Mørch‐Johnsen, Lynn; Holst, René; Tesli, Natalia; Bell, Christina; Lunding, Synve Hoffart; Rødevand, Linn; Werner, Maren Caroline Frogner; Melle, Ingrid; Andreassen, Ole Andreas; Lagerberg, Trine Vik; Steen, Nils Eiel; et al.
Abstract: Objective: Low total cholesterol has been linked with adverse mental symptoms such as aggression and impulsivity in severe mental disorders (SMDs). This putative association may affect the clinician's decision making about cholesterol lowering in this patient group. Here, we investigated the associations between cholesterol levels, aggression, and impulsivity in a large representative sample of in‐ and outpatients with SMD. Methods: Patients with schizophrenia‐ or bipolar spectrum disorders ( N  = 1 001) underwent thorough clinical characterization and blood sampling (total cholesterol, low‐density lipoprotein cholesterol, high‐density lipoprotein cholesterol). Aggression was characterized by the Positive and Negative Syndrome Scale Excited Component. Impulsivity was measured with the Barratt Impulsiveness Scale in a subsample of patients ( N  = 288). We used a multinomial logistic regression model to analyze the association between cholesterol and aggression and a multiple linear regression model to analyze the association between cholesterol and impulsivity, while controlling for confounders. Results: We found no significant associations between cholesterol levels and aggression or impulsivity. There were no significant interactions between cholesterol and diagnostic group or inpatient versus outpatient status. Controlling for medication use, body mass index, alcohol or illicit substance use did not affect the results. Conclusion: In this large sample of patients with schizophrenia‐ and bipolar spectrum disorders, we found no associations between cholesterol levels and aggression or impulsivity. This has clinical implications as patients with SMD are at increased CVD risk and currently undertreated with statins. Abstract : In context of the urgent need to improve cardiovascular health of patients with severe mental disorders, we investigated the associations between cholesterol levels and aggression in a sample of in‐ and outpatients with schizophrenia‐ and bipolar spectrum disorders. This large representative sample of patients with severe mental disorders revealed no significant associations between cholesterol levels and aggression or impulsivity.